Increasing the Learning Activities of Class V Students Through an Experimental Approach in Science Learning Using the Spiral Cycle - Riduan Riduan; Asnita Hasibuan (Journal on Education, 2024)
This research intends to explore the influence of applying an experimental learning method to the learning activities of class V students in the context of learning Natural Sciences (Science). The research subjects were 32 fifth grade kids who had varied talents, consisting of 16 male students and 16 female pupils. The research design uses a spiral cycle scheme model with four phases, including planning, implementing activities, observing and reflecting. Data collecting procedures involve documentation, tests, observations, and interviews. The research results showed that in cycle I, the average student learning activity reached 75%, with 77% of students traditionally achieving high activity. After implementing adjustments in cycle II, there was a considerable rise with the average student learning activity reaching 85%, and 85% of students traditionally achieving high activity. These findings indicate that employing an experimental learning approach can have a positive impact on students' learning activities and their enthusiasm in scientific study. Recommendations for this research include continuing to examine and develop experimental learning methodologies as well as adopting adjustments based on analysis of research outcomes to improve the quality of scientific learning at the primary level.